Implementation of Remission Granting to Prisoners at the Permisan Nusa Kambangan Penitentiary - Desya, Virjiqia Ananda; Miskiah, Siti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Remission is a right granted to prisoners who meet certain requirements while serving their sentences. This study discusses the process of granting remission at Permisan Class IIA Prison in Nusakambangan, which has stricter regulations compared to other prisons. Based on Law Number 22 of 2022 on Corrections, remission must meet administrative and substantive requirements, such as demonstrating good behavior and participating in rehabilitation programs. This study employs a qualitative method with a juridical-normative approach to analyze regulations and the implementation of remission policies at Permisan Prison. The findings indicate that remission at Permisan Prison is more selective due to the high number of inmates convicted of serious crimes. Additionally, transparency in the remission process has been enhanced through digitalized administration, including the use of barcodes and electronic signatures to prevent document manipulation. However, challenges remain, such as controversies over granting remission to serious crime offenders, necessitating regular evaluations of its implementation. This study concludes that remission is not only a form of reward for inmates but also an instrument to encourage rehabilitation and social reintegration while maintaining fairness for society.